2014
DOI: 10.1155/2014/415187
|View full text |Cite
|
Sign up to set email alerts
|

Pleasant/Unpleasant Filtering for Affective Image Retrieval Based on Cross-Correlation of EEG Features

Abstract: People often make decisions based on sensitivity rather than rationality. In the field of biological information processing, methods are available for analyzing biological information directly based on electroencephalogram: EEG to determine the pleasant/unpleasant reactions of users. In this study, we propose a sensitivity filtering technique for discriminating preferences (pleasant/unpleasant) for images using a sensitivity image filtering system based on EEG. Using a set of images retrieved by similarity ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…While the AMI features capture non-linear interactions between inter-electrode amplitude-amplitude coupling patterns, the Pearson correlation coefficient between the patterns can also be used to quantify the coherence, or linear interactions between the patterns. Spectral coherence measures have been widely used in EEG research and were recently shown to also be useful for affective state research (e.g., Kar et al, 2014 ; Xielifuguli et al, 2014 ). Hence, we explore the concept of amplitude modulation coherence, or AMC as a new feature for affective state recognition.…”
Section: Methodsmentioning
confidence: 99%
“…While the AMI features capture non-linear interactions between inter-electrode amplitude-amplitude coupling patterns, the Pearson correlation coefficient between the patterns can also be used to quantify the coherence, or linear interactions between the patterns. Spectral coherence measures have been widely used in EEG research and were recently shown to also be useful for affective state research (e.g., Kar et al, 2014 ; Xielifuguli et al, 2014 ). Hence, we explore the concept of amplitude modulation coherence, or AMC as a new feature for affective state recognition.…”
Section: Methodsmentioning
confidence: 99%
“…This translates into the necessity that samples that belong to the same individual appear close to each other, according to a concrete distance and in relation to samples coming from different subjects. To test if this condition holds for our data, we have computed the cosine distance (D C ) between all pairs of samples in each dataset, in line with other research works that have remarked on the benefits of this distance in specific contexts [50], [51]. This has been computed as:…”
Section: Distance Based Analysismentioning
confidence: 99%